(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The exchange rate and inflation indicators reflect how expensive or cheap this monetary resource will be for society or business entities. Given Georgia’s transitional and open economy, which is also dependent on imports and the national currency is pegged to the US dollar with a floating exchange rate, the price of these resources is volatile over time. The given dynamics in the last 30 years are typical for both standard and crisis periods. To define economic stability, we will use the following indicators within the scope of this work – Gross Domestic Product (GDP), inflation and national currency exchange rate. We need to focus on the last two indicators for the sake of this research. For individuals and legal entities, these data are essential for their short, medium and long-term activities – accumulation and spending of monetary resources, purchases, sales, demand allocations, etc. The study considers two major crises, which Georgia went through in the form of a typical crisis with the 2008 Russia- Georgia war. It continues as an atypical crisis due to the COVID-19 pandemic and the Russia-Ukraine war. Both events significantly impacted on our country’s inflation rate and the national currency exchange rate. Accordingly, it will be interesting to determine what kind of correlation was revealed in the first crisis and what new correlation was formed within the second indefinite crisis. As a result of regression and correlation analysis, it has been determined what contribution the monetary policy rate had in managing the mentioned crises and how much it helped Georgia’s economy. In particular, the influence of the monetary policy rate on the exchange and inflation rates has been studied.